Antimicrobial activity studies of the metal complexes derived from substituted cyclobutane substituted thiazole Schiff base ligands - Çukurovali, A; Yilmaz, I; Özmen, H (Kluwer Academic Publ, 2001)
Two novel bidentate Schiff base ligands derived from 4-(1-methyl-1-mesitylcyclobutane-3-yl)-2-aminothiazole (LH) have been prepared and characterized by elemental analyses, i.r., C-13- and H-1-n.m.r. spectra, u.v.-vis. and magnetic susceptibility measurements. The complexes are mononuclear. Antimicrobial activities of the ligands and their complexes have been tested: Bacillus megaterium DSM 32, Candida albicans FMC 17, Enterobacter aeroginosa CCM 2531, Escherichia coli ATCC 25922, Listeria monocytogenes SCOTTA, Micrococcus luteus LA 2971, Proteus vulgaris FMC 11, Pseudomonas aeruginosa DSM 50071, Saccharomyces cerevisiae FMC 16 and Staphylococcus aureus COWAN I. The thermal properties of the ligands and their complexes have been studied by t.g.a.